Linking "values" to EU trade policy—a good idea?. Issue 5 (28th December 2021) - Pelkmans, Jacques
Abstract: Should EU values be pursued by means of EU trade policy or separately via other policies? Article 21/3 TEU instructs the Council and the Commission to 'ensure consistency between the different areas of its external action', often (mis?)interpreted as a merger of all external policies with respect to values. Is this "merger" justified by the EU public interest? Linkage advocates are interested in the clout of EU trade and investment policy, but not in its objectives. Detailed recent research shows no empirical evidence of the effectiveness of value linkages. Thus, coupling values and EU trade policy may be costly and has few, if any, advantages; its main effect is continuous attention being paid to these issues (seen as a virtue by some). This article includes illustrations concerning the EU–Canada Comprehensive Economic and Trade Agreement (CETA), EU/China cooperation on sustainable development and the Comprehensive Agreement on Investment (CAI).